Why should athletes brake fast? Influence of eccentric velocity on concentric performance during countermovement jumps at different loads - Hernández-Davó, J. L.; Sabido, R.; Omar-García, M.; Boullosa, D. (International Journal of Sports Physiology and Performance, 2024)
Purpose: The aim of the present study was to analyze the effect of different eccentric tempos on eccentric kinetics and kinematics and the subsequent concentric performance when performing countermovement jumps against different loads.